Caracterização de um modelo numérico utilizando FDTD para uso em processos de aquecimento por micro-ondas em cavidades multimodo - Araújo, Magno Medeiros de (2015)
The microwave heating is largely used on industry, for treatment of ores and wood drying, and on food production. Besides this industry use, researches applied to cancer cells treatment, demonstrates that the microwave heating is more effective than regular procedures, such as, chemotherapy and radiotherapy, because it is a directional action and does not presents the same side effects amount. This work aims to develop a numeric model using FDTD in order relate the microwave spread, with the dielectric material heating on industry applications, standing as a base to future development of a software, which can study the microwave effects on these applications. Initially the basic issues involving the propagation of electromagnetic waves are discussed, as well as the equation that govern it. Then the mathematical treatment is performed, in order to related the known parameters to those obtained on the simulation. Lastly, experiments based in the simulated medium were performed, for the purpose of verify the error presented on the developed model. Those experiments allowed to conclude that the results numerically given, serve as a reference to situations where high precision is not necessary on the final temperature of the dielectric medium